2018
DOI: 10.1080/15475441.2018.1520639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Early Comprehension of Action Verbs

Abstract: This study was part of the interdisciplinary project IP-13 on "Towards a model for the incremental co-development of linguistic and conceptual representation of actions" at the Cluster of Excellence Cognitive Interaction Technology "CITEC"' (EXC 277), Bielefeld University funded by the German Research Foundation (DFG). We are grateful to the participating children and their parents, to Elena Justus for piloting the study and making the audio recordings, and to Marc Rohlfing and Malte Schilling for their data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Our study indicates that PRG enhanced children's long-term word production in general, but no differences in learning nouns versus verbs were found. These findings are somewhat surprising considering that literature points out that the acquisition of verbs requires more complexive attributes than nouns (Nomikou et al, 2019). While nouns can be drawn from relatively established referential frames, verbs refer to events that are complex and less transparent to single out concrete semantic features (e.g., Gentner, 1982;Hirsh-Pasek and Golinkoff, 2006;Heller and Rohlfing, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our study indicates that PRG enhanced children's long-term word production in general, but no differences in learning nouns versus verbs were found. These findings are somewhat surprising considering that literature points out that the acquisition of verbs requires more complexive attributes than nouns (Nomikou et al, 2019). While nouns can be drawn from relatively established referential frames, verbs refer to events that are complex and less transparent to single out concrete semantic features (e.g., Gentner, 1982;Hirsh-Pasek and Golinkoff, 2006;Heller and Rohlfing, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Summarizing the existing research, Rohlfing (2019) points to the evidence that gestures support the learning of various word classes: nouns, verbs, and prepositions. While the acquisition of various word classes benefit from iconic gestures, the GSA framework, which is based on the idea that gestures arise from underlying motor or visual imagery, suggests that verbs require “complexive” attributes ( Nomikou et al, 2019 , p. 9) that might be better reflected in a multimodal way. This suggestion is grounded in empirical evidence that shows, for example, that children gesture more when describing a verb compared to a noun ( Hostetter and Alibali, 2008 , 2019 ; Lavelli and Majorano, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cross-linguistic and cross-contextual examination of the semantic pluripotency hypothesis, it is worthwhile to investigate whether there is a semantically undifferentiated phase in other parts of speech (e.g., action words), as there is in object words. Surprisingly, Nomikou, Rohlfing, Cimiano, and Mandler (2019) reported that German 10-month-olds, unlike 9-month-olds, could recognize image stimuli corresponding to action words based solely on objects (e.g., an image of a banana for "eating"). Therefore, early words might initially encompass undifferentiated event categories, regardless of nouns or verbs.…”
Section: Do Other Parts Of Speech Also Have Pluripotent Characteristi...mentioning
confidence: 98%
“…In the first step of verifying the semantic pluripotency hypothesis, we regard event categories as the undifferentiated fusion of objects and actions. In this thesis, we primarily focus on the meanings of early common nouns among various parts of speech because common nouns (or object words) have been considered fundamental to word learning, and because most studies on word comprehension have been conducted with nouns (Nomikou, Rohlfing, Cimiano, & Mandler, 2019;Tomasello, 2003). For decades, object words have been conventionally regarded as meaning specific object categories during early word acquisition.…”
Section: The Semantic Pluripotency Hypothesis: a New Perspective On E...mentioning
confidence: 99%